Faktor Pengendali Lingkungan yang Membentuk Struktur Komunitas Plankton di Berbagai Ekosistem Pesisir Kawasan Konservasi Perairan Sekotong, Indonesia - Widia Tri Utami; Chandrika Eka Larasati; Paryono; Raja Aditya Sahala Siagian; Kara Muriel Angela Majerus (Universitas Mataram, 2026)
Plankton are crucial biological components driving the marine food web. This study aims to analyze the plankton community structure and identify the environmental drivers across diverse coastal ecosystems in Batu Putih Village, Sekotong Marine Protected Area (MPA), West Lombok. Field sampling was conducted in October 2025 across ten observation stations (encompassing mangrove, seagrass, coral reef, and anthropogenic zones) using a purposive sampling method. Data analysis included abundance, ecological indices (), and multivariate modeling via Canonical Correspondence Analysis (CCA). The results revealed that phytoplankton abundance ranged from 27 to 139 ind/L, peaking at the port area (ST10) and reaching its lowest in the coral reef ecosystem (ST5). Zooplankton abundance varied from 5 to 86 ind/L, with the highest concentration found in the mangrove ecosystem (ST8) and the lowest at ST1. The Bacillariophyceae (diatoms) and Copepoda groups emerged as the most dominant taxa. Generally, the diversity index was moderate with high evenness and low dominance, reflecting a relatively stable community. However, a community structure anomaly occurred at ST8, marked by a sharp decline in evenness () driven by the dominance of specific genera. The CCA ordination demonstrated that nitrate, phosphate, temperature, pH, and dissolved oxygen (DO) are the primary environmental drivers governing the spatial distribution of plankton. These findings indicate that while coastal waters generally support a stable community, anthropogenic-driven water quality fluctuations in specific zones could trigger ecological vulnerabilities. Consequently, continuous monitoring of water quality and managing domestic waste disposal are crucial to ensuring the long-term sustainability of the Sekotong MPA.